Establishing priorities for diabetes action goals according to key opinion leaders and health professionals - Dana Zelnik Yovel; Orly Tamir; Elza Lavon; Tanya Kolobov; Anat Bel-Ange; Michal Julius; Itamar Raz; Micha Rapoport (BMC, 2022)
Abstract Background The ever-increasing burden of diabetes and the limited resources highlight the need for prioritization of national action goals for diabetes management. The Israeli National Diabetes Council (INDC) initiated a prioritization process aiming to set a top list of diabetes related goals, as suggested by decision makers and health professionals. Methods A 2-step prioritization process, including a small (n = 32) circle of key opinion leaders of the INDC and a larger (n = 195) nationwide circle of diabetes health professionals consisting of physicians, nurses, and dieticians working in diabetes care centers, hospitals and family practice clinics, was established. An online questionnaire presenting 45 different action areas in diabetes prevention and care was distributed to the INDC members who ranked the 3 top diabetes priorities based on their individual interpretation of importance and applicability. The 7 highest ranking priorities were later presented to hospital-based and community diabetes health professionals. These professionals selected the 3 top priorities, based on their perceived importance. Results Council members opted mostly for action areas regarding specific populations, such as clinics for adult type-1 diabetes patients, diabetic foot, and pediatric and adolescent patients, while the health professionals' top priorities were mostly in the general field of prevention, namely high-risk prediabetes population, prevention of obesity, and promotion of healthy life-style. In addition, priorities differed between hospital and community health professionals as well as between different professional groups. Conclusions A national prioritization process of action areas in diabetes prevention and care is attainable. The resulting item list is affected by professional considerations. These priorities may direct efforts in the implementation of interventions to improve national-level diabetes management.